Phospholipid ether analogs for the detection of colorectal tumors. - Dustin A Deming; Molly E Maher; Alyssa A Leystra; Joseph P Grudzinski; Linda Clipson; Dawn M Albrecht; Mary Kay Washington; Kristina A Matkowskyj; Lance T Hall; Sam J Lubner; Jamey P Weichert; Richard B Halberg (PLoS ONE, 2014)
The treatment of localized colorectal cancer (CRC) depends on resection of the primary tumor with adequate margins and sufficient lymph node sampling. A novel imaging agent that accumulates in CRCs and the associated lymph nodes is needed. Cellectar Biosciences has developed a phospholipid ether analog platform that is both diagnostic and therapeutic. CLR1502 is a near-infrared fluorescent molecule, whereas 124/131I-CLR1404 is under clinical investigation as a PET tracer/therapeutic agent imaged by SPECT. We investigated the use of CLR1502 for the detection of intestinal cancers in a murine model and 131I-CLR1404 in a patient with metastatic CRC. Mice that develop multiple intestinal tumors ranging from adenomas to locally advanced adenocarcinomas were utilized. After 96 hours post CLR1502 injection, the intestinal tumors were analyzed using a Spectrum IVIS (Perkin Elmer) and a Fluobeam (Fluoptics). The intensity of the fluorescent signal was correlated with the histological characteristics for each tumor. Colon adenocarcinomas demonstrated increased accumulation of CLR1502 compared to non-invasive lesions (total radiant efficiency: 1.76×10(10) vs 3.27×10(9) respectively, p = 0.006). Metastatic mesenteric tumors and uninvolved lymph nodes were detected with CLR1502. In addition, SPECT imaging with 131I-CLR1404 was performed as part of a clinical trial in patients with advanced solid tumors. 131I-CLR1404 was shown to accumulate in metastatic tumors in a patient with colorectal adenocarcinoma. Together, these compounds might enhance our ability to properly resect CRCs through better localization of the primary tumor and improved lymph node identification as well as detect distant disease.